Hubungan Footprint Test Terhadap Q Angle pada Remaja Usia 12-15 Tahun di SMP Muhammadiyah 2 Gamping Yogyakarta - Anniza, Meiza; MAYANGSARI, RINA (Jurnal VARIDIKA, 2020)
Footprint test is an examination used to determine the level of the Medial Longitudinal Arch (MLA) by observing the medial border of the foot. This measurement is performed to identify deformities in the foot, such as flatfoot. This condition can become a problem if the shape of the feet does not change towards normal with age. Since the foot is the most distal region, a change in this region will be followed by a change in a more proximal region. Q angle is an important factor in assessing knee function. This research was conducted to determine the relationship between the footprint test and q angle in adolescents aged 12-15 years at SMP Muhammadiyah 2 Gamping Yogyakarta. This type of research is an analytic survey using a cross sectional approach. The population in this study were students of SMP Muhammadiyah 2 Gamping who had met the inclusion criteria. The sampling technique in this study was purposive sampling with a total sample of 51 students. From the results of the bivariate analysis with the chi square correlation test, the value of p = 0.022 (p 0.05) was obtained. This shows that Ho was rejected and Ha was accepted. Based on the objectives and research results, it can be concluded that there is a relationship between Footprint Test and Q Angle in adolescents aged 12-15 years at SMP Muhammadiyah 2 Gamping Yogyakarta. Keywords: footprint test, flatfoot, Q angle, MLA.